Country of origin effect and the impact of brand nationality on the perception of quality in the luxury goods market - Dittertová, Silvie (2015)
The purpose of this Master's Thesis is to investigate the attitudes of high net worth individuals toward country of origin information within the luxury goods market with respect to the quality of the products. The primary method used for the research is qualitative research based on in-depth interviews. Based on these in-depth interviews, the thesis demonstrates the synergy between the literature on country of origin and luxury goods and the consumers' quality perception on luxury based on country of origin.